(untitled) (Global Journal of Medical Research, 2024)
Cleft palate is the most common cause of velopharyngeal dysfunction (VPD), and primary palatoplasty should aim to establish the anatomical and functional conditions for adequate closure of the velopharyngeal mechanism during speech. The most common symptoms of VPD are hypernasality, characterized by excessive nasal resonance in the production of normally non-nasalized sounds due to the inability of the velopharyngeal sphincter to remain closed enough to prevent nasal resonance of orally articulated sounds; nasal air emission, characterized by the inappropriate escape of air through the nose during the production of pressure consonants, which may or may not be audible; and compensatory articulation disorders, considered strategies developed by individuals, replacing orally articulated sounds with those articulated in places posterior or superior to the velopharyngeal sphincter to compensate for the inability to impose pressure on the oral cavity and avoid pressure loss during speech.